Pengaruh Teman Sebaya Terhadap Minat Belajar Siswa Kelas X MA Plus Nurul Huda - Habibah, Idazar (Arden Jaya Publisher, 2023)
This study aims to determine the effect of peers on class X students' interest in learning at MA Plus Nurul Huda Bekasi City. The research method used is associative quantitative method. The sampling technique used a saturated sample with a sample size of 30 students at MA Plus Nurul Huda Bekasi City. The data used is simple linear regression analysis. Based on the research results, the hypothesis test calculation obtained tcount of -2.140 . This means that t_count> t_table, namely -2. 140> 2.048 then Ho is rejected and Ha is accepted, meaning that Peers have a significant effect on Learning Interest. Then based on the results of the determination coefficient test, it can be seen that the determination coefficient obtained is 0, 141, this means that 14.1% of peers (X) can be explained by the learning interest variable (Y), while the remaining 4.1% is influenced by other variables not examined in this study. The results of this study provide important meaning for the development of educational policies, especially those related to peer association in the school environment.